2021
DOI: 10.1021/jasms.1c00060
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between High-Resolution Native and Glycopeptide-Centric Mass Spectrometric Approaches: A Case Study into the Glycosylation of Erythropoietin Variants

Abstract: Glycosylation represents a critical quality attribute modulating a myriad of physiochemical properties and effector functions of biotherapeutics. Furthermore, a rising landscape of glycosylated biotherapeutics including biosimilars, biobetters, and fusion proteins harboring complicated and dynamic glycosylation profiles requires tailored analytical approaches capable of characterizing their heterogeneous nature. In this work, we perform in-depth evaluation of the glycosylation profiles of three glycoengineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Interestingly, our reconstruction based on glycopeptide data generally showed fewer low abundance and/or heavily glycosylated species than the top-down data, especially for the more heterogeneous RBDs. Such discrepancies were consistently reported in several recent studies of RBD/spike glycosylation, 33 , 45 and with other glycoprotein analysis, 49 to differing extents. Given the known experimental biases in glycopeptide analysis, incorporating top-down data will be highly valuable for more accurate characterization of glycosylation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, our reconstruction based on glycopeptide data generally showed fewer low abundance and/or heavily glycosylated species than the top-down data, especially for the more heterogeneous RBDs. Such discrepancies were consistently reported in several recent studies of RBD/spike glycosylation, 33 , 45 and with other glycoprotein analysis, 49 to differing extents. Given the known experimental biases in glycopeptide analysis, incorporating top-down data will be highly valuable for more accurate characterization of glycosylation.…”
Section: Discussionsupporting
confidence: 68%
“…After quantifying intact O-glycoforms and unexpected PTMs of all four RBDs from the intact mass and top-down data, we examined bottom-up glycopeptide (Figures S15–S18) and released glycan data (Figures S19 and S20; Tables S1–S4) regarding their coverage of glycosylation. Overall, released N-glycans showed similar glycan profiles to glycopeptide data but captured few N-glycans with sialic acids, possibly due to the labile nature or detection bias of sialic acid groups. , Thus, we focused on combining the RBD intact masses after N-glycan removal (O-glycoforms) with the N-glycopeptide data for reconstruction of the mass distributions for each RBD by adapting the method reported by Yang et al Figure plots the intact mass profile after peak filtering (top, black trace) with the corresponding reconstruction (bottom, red trace). Matching the reconstruction allowed us to attach assignments to at least half of the peaks in the filtered intact mass distributions including the selected glycoforms in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the issues of mass degeneracy preclude confident annotation of O-glycoforms of reporters expressing more than one type of O-glycan structures. However, intact measurements avoid known ionization bias of glycopeptides versus peptides, resulting in an underestimation of glycosite occupancy ( 45 , 86 ). Therefore, a combined approach with intact MS for quantitative assessment of O-glycosylation landscape and bottom–up glycopeptide analysis for O-glycosite identification represents the most promising future avenue to unravel the complexities of mucin and mucin-like domain O-glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…The N-glycosylation profile has been shown to differ dramatically depending on the protein construct employed, i.e., full-length spike, S1 domain, or receptor binding domain [ 33 , 34 ], and the cell type used for recombinant protein production. Recent charge detection MS measurements of the intact spike trimer indicate a glycan mass ~ 40% higher [ 35 ] than that reported in proteomic studies, akin to the discrepancy observed for erythropoietin [ 36 ].…”
Section: Resultsmentioning
confidence: 99%